Pengaruh Atribut Produk Wisata, Harga, Dan Aksebilitas Terhadap Keputusan Berkunjung Wisatawan Di Boon Pring Kabupaten Malang - Ummah, Lafifatul; Farida, Eka; Rahman, Fahrurrozi (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to examine and explain the influence of tourist product attributes, prices, and accessibility on tourists' visiting decisions in Boon Pring, Malang district. The research used is a quantitative method. The sampling technique uses the formula from Malhotra with the calculation results of 60 samples. The data testing technique used is multiple linear regression analysis by conducting validity tests, reliability tests, normality tests, classical assumption tests, hypothesis testing and coefficient of determination tests (R2).. In this research, it was found that tourism product attributes, price and accessibility were significantly influenced by the decision to visit. Keywords: Tourism Product Attributes, Prices, Accessibility. Decisions of Visiting Tourists in Boon Pring Malang Regency